Učinkovitost uporabe ortoz za spodnje ude pri otrocih s cerebralno paralizo (CP) - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2019)
Efficient walking function is an important therapeutic goal in children with cerebral palsy (CP). The use of orthosis is a generally accepted therapeutic measure to establish or improve gait pattern. The process of selecting the appropriate model and fine tuning of the individual orthosis with regard to the specifics of each individual child in daily clinical practice remains quite complex and demanding. In addition, there are still no sufficiently precise protocols in the literature for selecting the model and technical characteristics of the orthoses. Hence, we wanted to find evidence of effective use of orthoses for children with CP over the last ten years, which could add to the present knowledge and understanding. We searched the PubMed database for articles from 2008 to 2018 (key words child, cerebral palsy and orthosis). We found 192 original articles and 32 review articles; according to exclusion criteria, we selected 26 original articles and three review articles; three additional review articles were found later. Since the publication of the document issued by the International Society for Prosthetics and Orthotics in 2008, some new research results on ankle-foot orthoses have been published, but we can conclude from the presented results that the recommendations remain the same.
Keywords: Cerebral Palsy; cerebralna paraliza; lower limb; orthosis; Orthotic Devices; ortoze; pregled; rehabilitation; review; spodnji ud